Porous asphalt mixture with large air voids - Lim, Ee Hoe (2015)
Porous asphalt mixture has potential to be a safer and more suitable substitute for pavement for pedestrian and cyclist use. A study was carried out to investigate the influence of different gradations on the abrasion resistance, cohesiveness and asphalt flow of porous asphalt mixture (PAM). Three different gradations (G1, G2 and G3) were selected to be compared. Different tests were carried out on the samples of different gradations to contrast their abrasion resistance and cohesiveness. They include Cantabro Test and Draindown Test. The results of the Cantabro Test are testing the abrasion resistance of the pavement samples while the Draindown Test provides a sense of cohesiveness and asphalt flow. Low abrasion resistance and cohesiveness, and high asphalt flow are undesirable. Three compacted samples were produced for each gradation for Cantabro Test while 2 loose samples were produced for each gradation for Draindown Test. Cantabro Test and Draindown Test showed that Gradation 1, the one with most fines proportion produced samples of the highest abrasion resistance and cohesiveness, and also the lowest asphalt flow. In conclusion, Gradation 1 is selected as the best gradation among the three gradations and with sufficient binder content, a finer gradation would produce asphalt mixes of higher abrasion resistance and cohesiveness, and lower asphalt flow.